DOES CERTAINTY OF DIVINE FORGIVENESS PREDICT THE DISTINCT PSYCHOLOGICAL EFFECTS OF PARTICIPATING IN THE CATHOLIC RITUAL OF CONFESSION? - Fakir, Kryschelle Lysa Ann (Wake Forest University, 2026)
The Catholic Sacrament of Confession is unique among religious disclosure practices in that the priest absolves penitents of their sins, offering certainty of divine forgiveness and in turn producing distinctive psychological effects such as relief from shame and guilt, increased gratitude and peace, and greater negative emotions during confession. Comparably, personal prayer involves disclosure to God without a human intermediary to confirm forgiveness. To test the theory that certainty of divine forgiveness produces distinctive effects, the present study employed a within-subjects design where Catholic participants engaged in confession, private prayer, and a control condition, each for one week in counterbalanced order. A total of 89 individuals from the Psychology SONA pool and the Wake Forest University Catholic Community were recruited. Primary analyses used multivariate analysis of variance (MANOVA) to compare conditions on psychological outcomes. Results from the analyses showed that confession only predicted greater negative emotions during confession compared to personal prayer and the control, suggesting greater costs associated with confession. However, across all outcomes, participants reported greater benefits (i.e., relief from shame and guilt, greater feelings of peace, gratitude, and humility) after engaging in any religious intervention. These results contribute to the growing literature on the psychological effects of religious practices.
Keywords: Catholicism; Confession; Divine Forgiveness; Prayer; Psychology; Religion